Antibacterial activity of neem (Azadirachta Indica) extracts against multiple drug resistant (MDR) bacteria - Ng , Yin Boon (2012)
This study concerned with the evaluation of antibacterial activity of four crude extracts of three parts (leaf, root and bark) of Neem (Azadirachta Indica) obtained by four solvents (chloroform, acetone, cold and hot ethanol). The antibacterial activity of these extracts was assessed against two multiple-drug-resistance bacteria strains, namely E. coli and S. aureus by the conventional well diffusion method. For the antibacterial bioassay, four concentrations (0. 1, 0.2, 0.4 and 0.8%) of each solvent and -part extract solutions were prepared; DMSO was used to solubilize the extract in water. 1% of DMSO was used as control. All extracts were active against both test organisms E. coli and S .aureus, the root acetone displayed overall more potent activity and reaches 52.5% and 51.88% respectively with concentration of 0.8% and the lowest activity observed with bark hot ethanol at concentration of 0.8%. Bioactive groups such as alkaloids and sesquiterpene lactones were screened by thin layer chromatography; and the results obtained were negative for alkaloids and positive for sesquiterpene lactones. The experimental results obtained from this study suggest that Neem (Azadirachta Indica) extracts are promising as natural antibacterial and this may warrant further research to determine the bioactive compound (s).